1997
DOI: 10.1203/00006450-199701000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Face Mask, Head Hood, and Canopy for Breath Sampling in Flow-Through Indirect Calorimetry to Measure Oxygen Consumption and Carbon Dioxide Production of Preterm Infants <1500 Grams

Abstract: Complete sampling of expired air is essential for accurate O2 consumption(CO2 production) [VO2(VCO2)] measurements with flow-through indirect calorimetry. In preterm infants complete sampling is critical, because only low sampling flows can be used. The accuracy of the various breath sampling systems at low flows and their patient compatibility is untested. We therefore measured 1) the accuracy of VO2(VCO2) measurements with a face mask, a head hood, and a canopy in vitro at low sampling flows; 2) the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…We have previously shown that the collection of exhaled gas with a sampling device held close to the infant's face but without actually touching it does not result in increased unrest or changes in body temperature (8). During the present measurements, the infants were sleeping 85% of the time.…”
Section: Use In the Clinical Settingmentioning
confidence: 63%
See 3 more Smart Citations
“…We have previously shown that the collection of exhaled gas with a sampling device held close to the infant's face but without actually touching it does not result in increased unrest or changes in body temperature (8). During the present measurements, the infants were sleeping 85% of the time.…”
Section: Use In the Clinical Settingmentioning
confidence: 63%
“…all expired air comes out of the ventilated infant's mouth and nose, the methanol burner was placed inside a manikin the size of a preterm infant with the methanol flame burning at the position of the manikin's mouth. The manikin is described in detail elsewhere (8). Gas was sampled by holding the breath collector with the bottom opening above the manikin's face while mechanical ventilation was simulated at a rate of 60/min, PIP of 15 cm H 2 O, PEEP of 3 cm H 2 O (Fig.…”
Section: Protocol For the In Vitro Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…This canopy is commercially available for use on the new-born infant (Datex Division Instrumentarium Corp.). Canopy was used to provide the best patient's compatibility, also some observations suggested a variability of measurements using the canopy, face mask or head hood (Bauer et al, 1997).…”
Section: Methodsmentioning
confidence: 99%